Phonological Basis of Mispronunciation in Spoken English of Kabarasi People in Social Setting - Chenenje, Solomon Luvonga (Asosiasi Dosen Perguruan Tinggi Islam, 2024)
The phonological basis of mispronunciation in spoken English by Kabarasi speakers in social settings includes voicing and devoicing, vowel insertion, substitution or avoidance, and syllable misplacement. The study adopted the contrastive analysis hypothesis theory by Khresheh (2016), which describes how errors are transferred from L1 to L2 and the degree of strength of errors transferred, whether positive or negative. The data was presented and analyzed in tables from which sounds of both English and Kabarasi were written. English has 25 consonant sounds, while Kabarasi has 23. Some sounds clash while others (voiceless) match, but the mismatch rate is higher than positive transfer, leading to errors in spoken English. Such errors can be minimized by practice in English elocution and oral skills based on minimal pairs. However, all the errors in spoken English by Kabarasi speakers can not be eradicated completely, provided that the utterer is a native speaker of Lukabrasi.